2020
DOI: 10.1111/1348-0421.12837
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of clinical Salmonella enterica serovar Typhimurium isolates from Thailand in a mouse colitis model

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium [STM]) is a leading cause of nontyphoidal salmonellosis (NTS) worldwide. The pathogenesis of NTS has been studied extensively using a streptomycinpretreated mouse colitis model with the limited numbers of laboratory STM strains. However, the pathogenicity of the clinically isolated STM (STMC) strains endemic in Thailand in mice has not been explored. The aim of this study was to compare the pathogenicity of STMC strains collected from Northern Thailand wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…Mice in the untreated control group were daily fed with sterile PBS. To induce colitis, 100 μL of (200 mg/mL) streptomycin sulfate (Sigma Aldrich, Singapore) solution was given orally to mice 1 day prior to STM infection (10 9 cfu of STM/mouse) ( Barthel et al, 2003 ; Sarichai et al, 2020 ). All mice were euthanized at day 4 post infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice in the untreated control group were daily fed with sterile PBS. To induce colitis, 100 μL of (200 mg/mL) streptomycin sulfate (Sigma Aldrich, Singapore) solution was given orally to mice 1 day prior to STM infection (10 9 cfu of STM/mouse) ( Barthel et al, 2003 ; Sarichai et al, 2020 ). All mice were euthanized at day 4 post infection.…”
Section: Methodsmentioning
confidence: 99%
“…Four days after the infection with STM, all mice were euthanized and tissue samples were collected for mRNA expressions by qPCR. Fold change (relative of expression) of important proinflammatory cytokine genes [ Kc , Ifng , and Il-6 encoding for KC or CXCL-1, interferon (IFN)-gamma and IL-6, respectively], Nos2 and Zo-1 [encoding for iNOS and a tight junction protein zonula occludens (ZO-1), respectively], were performed as previously described ( Sarichai et al, 2020 ). In short, collected tissues were immersed in RNA preservative solution (RNAstore reagent, TIANGEN, China) and stored at −20°C until extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella is a common bacterial type that severely impacts the feed supply chain and various food production industries 7 . It has been reported that thousands of people die worldwide from Salmonella systemic infections like non-typhoidal salmonellosis (NTS), brain culminating in meningitis, and associated neurological abnormalities 812 . Moreover, Salmonella continues to be the second biggest cause of foodborne disease in the United States and the leading cause of both hospitalization and deaths 7 .…”
Section: Fig1mentioning
confidence: 99%
“…The mice were randomly divided into four groups with twelve mice in: Control group; LPS group; LPS+IOP group. To avoid infection by other bacteria, mice were pretreated with streptomycin [27]. A murine model of LPS-induced endometritis was established as previously reported [28].…”
Section: Experimental Processingmentioning
confidence: 99%